2006
DOI: 10.1182/blood-2006-03-012534
|View full text |Cite
|
Sign up to set email alerts
|

Development of a macrophage-based nanoparticle platform for antiretroviral drug delivery

Abstract: Complex dosing regimens, costs, side effects, biodistribution limitations, and variable drug pharmacokinetic patterns have affected the long-term efficacy of antiretroviral medicines. To address these problems, a nanoparticle indinavir (NP-IDV) formulation packaged into carrier bone marrow-derived macrophages (BMMs) was developed. Drug distribution and disease outcomes were assessed in immune-competent and human immunodeficiency virus type 1 (HIV-1)-infected humanized immune-deficient mice, respectively. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
241
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(243 citation statements)
references
References 48 publications
1
241
0
1
Order By: Relevance
“…To this end, we examined whether BMM could be used as vehicles for delivery of a potent antioxidant, catalase. Indeed, it has long been known that macrophages and microglia as well as other mononuclear phagocytes can endocytose colloidal nanomaterials, for example, liposomes or nanosuspensions, and subsequently carry and release the drug to site of tissue injury, infection, or disease (32,33,35,46,86).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we examined whether BMM could be used as vehicles for delivery of a potent antioxidant, catalase. Indeed, it has long been known that macrophages and microglia as well as other mononuclear phagocytes can endocytose colloidal nanomaterials, for example, liposomes or nanosuspensions, and subsequently carry and release the drug to site of tissue injury, infection, or disease (32,33,35,46,86).…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow cells extracted from murine femurs (C57BL/6, female mice) as described (32) were cultured for 10 days in the media supplemented with 1000 U/mL macrophage colonystimulating factor (MCSF) (a generous gift from Wyeth Pharmaceutical, Cambridge, MA). The purity of monocyte culture was determined by flow cytometry using FACSCalibur (BD Biosciences, San Jose, CA).…”
Section: Bmmmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies done in our laboratory using indinavir (IDV) nanosuspensions highlighted the importance of cell-based drug delivery for treatment of HIV disease [275][276][277]. When in an alkaline environment, IDV can be fabricated into nanosuspensions and remain stable.…”
Section: Cell-mediated Delivery Of Nanocarriers To the Brainmentioning
confidence: 99%
“…This in vitro in vivo study confirmed that PEO-PCL nanoparticles can incorporate SQN and deliver it intracellularly in Mo/Mac. In a novel follow-up to the concept of targeting nanoparticles to Mo/Mac, Dou et al (2006Dou et al ( , 2007 postulated that the mononuclear phagocytes, as the principal reservoir for viral dissemination, could also serve as a transporter of antiretroviral drugs themselves since they are responsible for dissemination of HIV that is, macrophages can enter into tissues that limit entry of many ARV drugs. In this novel study, they chose indinavir (IDV) to prove their concept of using a macrophage-based nanoparticulate system as a drug carrier itself.…”
Section: Nanoparticles For Arv Drug Therapymentioning
confidence: 99%